The effect of social norms on parents’ beliefs and food choices: Evidence from a lab-in-the-field experiment - Berlin, Noémi; Jaber-Lopez, Tarek; Sarr, Moustapha (Journal of behavioral and experimental economics, 2025)
In a lab-in-the-field experiment, we investigate the influence of social norms on 300 parents’ beliefs regarding the nutritional quality of food items and their subsequent food choices. We use a 3 × 2 between-subject experimental design where we vary two factors: 1 — the social norm provided to parents: a descriptive norm (what other parents choose) vs. an injunctive norm (what other parents approve of), and 2 — the recipient of the food decisions made by parents: their own child vs. an unknown child. Parents participate in a two-stage process. In the first stage, we elicit their beliefs regarding the nutritional quality of various food items and ask them to make a food basket without specific information. In the second stage, based on their assigned treatment, they receive specific information and repeat the belief elicitation and the food basket selection tasks. We find that only the descriptive norm significantly reduces parents’ overestimation rate of items’ nutritional quality. Injunctive norm significantly improves the nutritional quality of both, the parent’s and child’s baskets. Descriptive norm significantly improves the nutritional quality of child’s baskets only when parents are choosing for unknown child. •We investigate how social norms shape parents’ food beliefs and choices.•Descriptive norms reduce overestimation of food’s nutritional quality.•Injunctive norms improve food choices for both parents and children.•Parents adjust beliefs and food baskets after receiving specific information.•We test norms’ impact on choices for own vs. unknown child.